Results of intellectual activity Academician I.G. Petrovskii Bryansk state university in 2018 in the sphere of industrial property in the direction of «Engineering» - Bandurin R.A.; Khimich A.V. (Научно-технический вестник Брянского государственного университета)
The article discusses the results of intellectual activity in the field of industrial property, obtained by scientists of the Academician I.G. Petrovskii Bryansk State University in 2018. A description and analysis of the effectiveness of new technical solutions in relation to the designs of handling systems of mobile transport-technological machines and conveyors with a suspen-sion belt and distributed drive is given. A description is also given of computer programs for automating the design and modeling of work processes for the specified lifting and transport equipment.